Compressed sensing in li-fi and wi-fi networks - Benslama, Malek; Mokhtari, Hatem (London : ISTE Press Ltd., 2017)
Annotation This text features coverage of the first applications in optical telecommunications and wireless. After extensive development of basic theory, many techniques are presented, such as non-asymptotic analysis of random matrices, adaptive detection, greedy algorithms, and the use of graphical models.
Includes bibliographical references and index.
Vendor-supplied metadata.
Keywords: Coding theory; Data compression (Telecommunication); COMPUTERS / Computer Literacy; COMPUTERS / Computer Science; COMPUTERS / Data Processing; COMPUTERS / Hardware / General; COMPUTERS / Information Technology; COMPUTERS / Machine Theory; COMPUTERS / Reference; Coding theory; Data compression (Telecommunication); Electronic books